2016
DOI: 10.1038/srep35682
|View full text |Cite
|
Sign up to set email alerts
|

Association between allergic conditions and risk of prostate cancer: A Prisma-Compliant Systematic Review and Meta-Analysis

Abstract: Association between allergic conditions and prostate cancer risk has been investigated for many years. However, the results from available evidence for the association are inconsistent. We conducted a meta-analysis to evaluate the relationship between allergic conditions (asthma, atopy, hay fever and “any allergy”) and risk of prostate cancer. The PubMed and Embase databases were searched to screen observational studies meeting our meta-analysis criteria. Study selection and data extraction from included studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(181 reference statements)
1
7
0
1
Order By: Relevance
“…For example, in the metaanalysis conducted by Vojtechova et al, no association was found for any allergy (RR [95% CI] 1.01 [0.94-1.08]) or asthma (0.93 [0.73-1.19]) with breast cancer, pooling results from both retrospective (n case = 3,544) and prospective studies (n case = 7,192). There was no difference [10]. Consistent with these previous findings, we did not observe evidence in support for an association between allergy, asthma, and risk of breast or prostate cancer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, in the metaanalysis conducted by Vojtechova et al, no association was found for any allergy (RR [95% CI] 1.01 [0.94-1.08]) or asthma (0.93 [0.73-1.19]) with breast cancer, pooling results from both retrospective (n case = 3,544) and prospective studies (n case = 7,192). There was no difference [10]. Consistent with these previous findings, we did not observe evidence in support for an association between allergy, asthma, and risk of breast or prostate cancer.…”
Section: Discussionsupporting
confidence: 86%
“…Vojtechova et al aggregated data across 16 observational studies and found no evidence that allergy or asthma are associated with cancers of the breast (n case = 10,736; relative risk (RR) [95% confidence interval (CI)] 1.01 [0.94-1.08] for any allergy; 0.93 [0.73-1.19] for asthma) or prostate (n case = 7,890; 1.01 [0.87-1.17] for any allergy; 0.93 [0.76-1.15] for asthma) [9]. Similarly, Zhu et al combined data from 20 observational studies and found no association of allergy or asthma with prostate cancer (n case = 19,450; 0.96 [0.86-1.06] for any allergy; 1.04 [0.92-1.17] for asthma) [10]. Such findings, however, could have results due to attenuation to the null caused by measurement error or masking of a causal effect by confounders.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta‐analysis included case–control ( n = 5) and cohort studies ( n = 15), the RR for developing PrC risk was 1.04 (95% CI: 0.9–1.2) for asthma, 1.04 (95% CI: 0.9–1.1) for hay fever, 1.2 (95% CI: 0.7–2.1) for atopy, and 0.96 (95% CI: 0.8–1.1) for any allergy. When adjusted for potential confounders, that is, smoking, alcohol drinking, age, BMI and race, identical results were yielded 174 . In contrast, findings of a Mendelian randomization study did not provide any evidence to support association of allergic disease with PrC (OR = 1.00; 95% CI: 0.94–1.05) 97 .…”
Section: Allergy and Cancer Riskmentioning
confidence: 73%
“…Ã Denotes statistically significant result. findings and the link between asthma and prostate cancer remains unclear (27). Associations have been observed between appendicitis or appendectomy and several inflammatory or immune-related conditions: inverse for ulcerative colitis (12,14,28), MS (16), and coeliac disease (15); and positive for Crohn's disease (13,28).…”
Section: Discussionmentioning
confidence: 99%